Distribution Dynamics of Wide‐Ranged and Narrow‐Ranged Species From the Pliocene to the Future: Insights From Asian Endemic Holcoglossum (Orchidaceae) - Pei‐Yang Zhang; Peng Zhou; Yi‐Zhen Liu; Zhi‐Wen Xu; Lei‐Qiang Gong; Xiao‐Guo Xiang (Ecology and Evolution, 2025)
ABSTRACT Climate change is an important driver of the potential distribution changes of plants. However, the potential distribution changes of wide‐ranged and narrow‐ranged species in response to climate change were still controversial. An epiphytic orchid genus Holcoglossum is a key group to address this issue, with about 30% of species widely distributed in the Asian mainland, while the others are only narrowly distributed in special mountains. Combining with species' occurrences, the environmental variables, and Human Footprint data, we analyzed the key predictor variables and predicted the potential distributions and centroid shifts of four wide‐ranged and four narrow‐ranged Holcoglossum species from the Pliocene to the future using the maximum entropy (MaxEnt) model. Our results showed that the potential distributions of seven Holcoglossum species (except H. subulifolium) were mainly impacted by the precipitation of the warmest quarter in the future. From the Pliocene to the present, the potential distributions of the wide‐ranged species (except H. subulifolium) and the narrow‐ranged species were contracted. From the present to the future (SSP2‐4.5, 2090), the potential distributions of two wide‐ranged species (H. flavescens, H. himalaicum) would contract, whereas the other two would expand; the potential distributions of two narrow‐ranged species (H. kimballianum, H. wangii) would contract, and the other two would expand. The centroids of three wide‐ranged species would migrate southwards (H. amesianum, H. himalaicum, and H. subulifolium), whereas H. flavescens would have nearly no migration; the centroids of three narrow‐ranged species would migrate southwards (H. pumilum, H. quasipinifolium, and H. wangii), whereas H. kimballianum would migrate westwards. We found that the vulnerability to climate change of species might be unlinked to their current distribution range and the phylogenetic relationships. This study provides new insights for the potential distribution changes and conservation of narrow‐ranged and wide‐ranged orchid species.